Esophageal Cancer in Canada: Trends according to Morphology and Anatomical Location. (2012) - Otterstatter, Michael C; Brierley, James D; De, Prithwish; Ellison, Larry F; MacIntyre, Maureen; Marrett, Loraine D; Semenciw, Robert; Weir, Hannah K; for the Canadian Cancer Statistics Steering Committee,
Abstract : BACKGROUND: Esophageal adenocarcinoma has one of the fastest rising incidence rates and one of the lowest survival rates of any cancer type in the Western world. However, in many countries, trends in esophageal cancer differ according to tumour morphology and anatomical location. In Canada, incidence and survival trends for esophageal cancer subtypes are poorly known. METHODS: Cancer incidence and mortality rates were obtained from the Canadian Cancer Registry, the National Cancer Incidence Reporting System and the Canadian Vital Statistics Death databases for the period from 1986 to 2006. Observed trends (annual per cent change) and five-year relative survival ratios were estimated separately for esophageal adenocarcinoma and squamous cell carcinoma, and according to location (upper, middle, or lower one-third of the esophagus). Incidence rates were projected up to the year 2026. RESULTS: Annual age-standardized incidence rates for esophageal cancer in 2004 to 2006 were 6.1 and 1.7 per 100, 000 for males and females, respectively. Esophageal adenocarcinoma incidence rose by 3.9% (males) and 3.6% (females) per year for the period 1986 to 2006, with the steepest increase in the lower one-third of the esophagus (4.8% and 5.0% per year among males and females, respectively). In contrast, squamous cell carcinoma incidence declined by 3.3% (males) and 3.2% (females) per year since the early 1990s. The five-year relative survival ratio for esophageal cancer was 13% between 2004 and 2006, approximately a 3% increase since the period from 1992 to 1994. Projected incidence rates showed increases of 40% to 50% for esophageal adenocarcinoma and decreases of 30% for squamous cell carcinoma by 2026. DISCUSSION: Although esophageal cancer is rare in Canada, the incidence of esophageal adenocarcinoma has doubled in the past 20 years, which may reflect the increasing prevalence of obesity and gastroesophageal reflux disease. Declines in squamous cell carcinoma may be the result of the decreases in the prevalence of smoking in Canada. Given the low survival rates and the potential for further increases in incidence, esophageal adenocarcinoma warrants close attention.